2018
DOI: 10.1016/j.celrep.2018.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 5 Is Essential for Spermatogenesis in Zebrafish

Abstract: Highlights d hsf5 is predominantly expressed in testis d Hsf5 loss of function causes infertility in zebrafish males, but not in females d The hsf5 À/À mutant testes start showing defects from meiosis-I during spermatogenesis d The mutants have low sperm count with structural defects in their spermatozoa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
(48 reference statements)
0
21
0
Order By: Relevance
“…HSF5 belongs to the heat shock transcription factor family, which is involved in differentiation, reproduction, and stress-induced adaptation [14]. Previous studies have revealed that HSF5 plays a critical role in germ cell development and meiotic progression [24,38]. However, the functional characterization of HSF5 involved in cancer and the immune response has not been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSF5 belongs to the heat shock transcription factor family, which is involved in differentiation, reproduction, and stress-induced adaptation [14]. Previous studies have revealed that HSF5 plays a critical role in germ cell development and meiotic progression [24,38]. However, the functional characterization of HSF5 involved in cancer and the immune response has not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…However, HSF2 has appeared to decrease in a wide range of cancers and act as a tumor suppressor [22,23]. To date, only a few studies have focused on HSF5, and its detailed functional characterization in tumors has not been performed [24].…”
Section: Ivyspringmentioning
confidence: 99%
“…The transcripts of ar peak at 16 dpf and 22 dpf, and are subsequently maintained at a high stable level across the presumptive male development stage, suggesting that it is essential for male differentiation and maintenance [35] , [39] . Saju et al found that heat shock transcription factor family member 5 ( hsf5 ), whose expression increased from 35dpf, plays an important role in early stage of spermatogenesis and fertility in males [40] .…”
Section: Gene Network For Reproductive Development In Zebrafishmentioning
confidence: 99%
“…ar -null male zebrafishes appear with female secondary sex characteristics and are sterile, having smaller testes and blocked spermatogenesis [41] . hsf5 −/− mutant males are infertile with decreased sperm count, abnormal sperm morphology and decreased sperm motility, however, females are fertile [40] .…”
Section: Gene Network For Reproductive Development In Zebrafishmentioning
confidence: 99%
“…Under stress condition in poultries all heat shock factors are activated. In animals, four HSFs was known till 2018, when Saju and his collages found [31] the fth HSF, HSF5 in Danio rerio. This HSF5 is essential for the spermatogenesis in zebra sh.…”
Section: Introductionmentioning
confidence: 99%